Pivampicillin in treating genital infection with Chlamydia trachomatis. Issue 4 (August 1985) - Møller, B R; Cramers, M; From, E
Abstract : Pivampicillin was used to treat urogenital colonisation with Chlamydia trachomatis in 41 women and 24 men who yielded chlamydiae but not gonococci. They were treated for 10 days. All but one patient gave negative chlamydia cultures 10 days after the start of treatment, and all 65 patients gave negative results at the second examination seven days later. Ten days of treatment with pivampicillin seems to be the optimum to eradicate C trachomatis from the lower genital tract in man.